2012
DOI: 10.1371/journal.pone.0037962
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Optical Microscopy for Histology of Fresh Normal and Cancerous Pancreatic Tissues

Abstract: BackgroundPancreatic cancer is a lethal disease with a 5-year survival rate of only 1–5%. The acceleration of intraoperative histological examination would be beneficial for better management of pancreatic cancer, suggesting an improved survival. Nonlinear optical methods based on two-photon excited fluorescence (TPEF) and second harmonic generation (SHG) of intrinsic optical biomarkers show the ability to visualize the morphology of fresh tissues associated with histology, which is promising for real-time int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 31 publications
1
41
0
Order By: Relevance
“…27,28 Our previous work on exocrine pancreatic tissues using nonlinear optical microscopy has been reported, demonstrating that the acinar cells and extracellular matrix in fresh pancreatic tissues can be visualized by intrinsic TPEF signals from nicotinamide adenine dinucleotide (NADH) and flavin adenine dinucleotide (FAD) and SHG signals from collagen fibers, respectively. 29 This work did not manage to recognize sparse PSCs from dense acinar cells in tissue environment, though PSCs show long cytoplasmic processes compared with pyramidal acinar cells. 1 A recent study has reported Ca 2þ signaling events in PSCs stained with fluorescent calcium indicators, and the intrinsic fluorescence from cellular vitamin A in PSCs was also detected to show the morphology of PSCs in pancreatic tissues.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…27,28 Our previous work on exocrine pancreatic tissues using nonlinear optical microscopy has been reported, demonstrating that the acinar cells and extracellular matrix in fresh pancreatic tissues can be visualized by intrinsic TPEF signals from nicotinamide adenine dinucleotide (NADH) and flavin adenine dinucleotide (FAD) and SHG signals from collagen fibers, respectively. 29 This work did not manage to recognize sparse PSCs from dense acinar cells in tissue environment, though PSCs show long cytoplasmic processes compared with pyramidal acinar cells. 1 A recent study has reported Ca 2þ signaling events in PSCs stained with fluorescent calcium indicators, and the intrinsic fluorescence from cellular vitamin A in PSCs was also detected to show the morphology of PSCs in pancreatic tissues.…”
Section: Introductionmentioning
confidence: 92%
“…29 It is reported that the two-photon absorption of the major intrinsic fluorophores such as NADH and FAD decreases as the excitation wavelength increases in the range of 700 to 900 nm. 21 We tuned the excitation wavelength in the 730 to 890 nm range and found that 750 nm was the optimal wavelength to give the best signalto-noise ratio in our microscopic system.…”
Section: Nonlinear Optical Imaging and Spectral Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Fibrillar collagens possess a unique non-centrosymmetric structure allowing them to act as a frequency doubler when interacting with multiphoton laser light. This coherent, nonabsorptive light interaction process can be exploited to obtain high-resolution, quantifiable images of discrete collagen fibers in a number of sources including two-dimensional histopathology specimens, 16 three-dimensional intact tissues, 17 and live animal models 18 without the need for exogenous staining. Using second harmonic generation imaging, a number of groups have shown that changes in collagen fiber structure and organization during tumor initiation and progression have biological consequences and correlate with clinical outcomes in a number of other solid tumor types.…”
mentioning
confidence: 99%